The Influence Mechanism of the Master Weak Interlayer on Bench Blasting Effect and Its Evaluation Method - Senlin Nan (Shock and Vibration, 2021)
The weak interlayers in an open-pit blasting bench affect the uniform distribution of explosive energy. To explore the mechanistic influence of a weak interlayer on the effect of blasting, 9 sets of numerical blasting experiments were constructed using the orthogonal experiment method. The degree of bench crushing after blasting, the maximum velocity of the rock mass at 0.05 s, and the displacement of the back of the bench were thus investigated. The analysis revealed that the impact of the thickness of the weak interlayer, its wave impedance, and its location of occurrence on the bench blasting indicated an ordered decreasing effect. Based on this, the evaluation method for the master weak interlayer and the design plan of the specific charge structure were proposed. The evaluated design proposals were verified through both numerical and field tests. The research results will provide a scientific basis to determine a reasonable charge structure of the bench blasting of rock masses containing weak interlayers.